2019
DOI: 10.1371/journal.pone.0212238
|View full text |Cite
|
Sign up to set email alerts
|

Sediment potentially controls in-lake phosphorus cycling and harmful cyanobacteria in shallow, eutrophic Utah Lake

Abstract: Lakes worldwide are impacted by eutrophication and harmful algal or cyanobacteria blooms (HABs) due to excessive nutrients, including legacy P released from sediments in shallow lakes. Utah Lake (northern Utah, USA) is a shallow lake with urban development primarily on the east side of the watershed, providing an opportunity to evaluate HABs in relation to a gradient of legacy sediment P. In this study, we investigated sediment composition and P concentrations in sediment, pore water, and the water column in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…One reason for our position that nutrient prevention should be prioritized over attenuation is simply the immense fertilization capacity of our global society (Gruber and Galloway, 2008;Seitzinger et al, 2010). The capacity of ecosystems to assimilate or remove N and P can easily be overwhelmed by human nutrient inputs, and recovery from nutrient saturation can take decades to millennia (Dupas et al, 2018;Goyette et al, 2018;Haas et al, 2019;Randall et al, 2019). This raises the question of how can nutrient inputs be decreased while also achieving the sustainable development goal of eliminating malnutrition?…”
Section: Preventing Rather Than Curing Nutrient Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…One reason for our position that nutrient prevention should be prioritized over attenuation is simply the immense fertilization capacity of our global society (Gruber and Galloway, 2008;Seitzinger et al, 2010). The capacity of ecosystems to assimilate or remove N and P can easily be overwhelmed by human nutrient inputs, and recovery from nutrient saturation can take decades to millennia (Dupas et al, 2018;Goyette et al, 2018;Haas et al, 2019;Randall et al, 2019). This raises the question of how can nutrient inputs be decreased while also achieving the sustainable development goal of eliminating malnutrition?…”
Section: Preventing Rather Than Curing Nutrient Incontinencementioning
confidence: 99%
“…There are three general fates for nutrients moving through the soils, riparian zones, surface waters, and aquifers of a watershed: (1) Retention (i.e., a long or short-term delay) by biological and physical processes, including nutrient uptake, sorption, or hydrological residence time (Covino et al, 2010;Sebilo et al, 2013;Van Meter et al, 2016;Dupas et al, 2017;Ehrhardt et al, 2019), (2) Vertical removal to the atmosphere or lithosphere, including denitrification, aeolian transport, or mineral precipitation with various metals (Groffman et al, 2006;Seitzinger et al, 2006;Pinay et al, 2018;Randall et al, 2019), and (3) Longitudinal export from the watershed via surface or subsurface flow (Burt and Pinay, 2005;Seitzinger et al, 2010;Abbott et al, 2018a). The reactivity and mobility of organic and inorganic nutrients depend on and influence biogeochemical conditions (Abbott et al, 2016;Bernhardt et al, 2017), meaning that the fate of carbon, N, and P can vary substantially through time (e.g., storm events or seasons) and in space (e.g., different watersheds or biomes) (Dupas et al, 2016;Moatar et al, 2017;Musolff et al, 2017;Minaudo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that IP pred is driven by PC3, a specific combination of five lake characteristics. Given the importance of sediment characteristics (Hupfer and Lewandowski 2008;Randall et al 2019), incorporating specific fractions (e.g., fractions that are commonly associated with the sediment P release, Fe content, NĂŒrnberg 1988) may further increase the predictive power of the current model. Nevertheless, its current R 2 value was generally in a range of those that are reported for the models predicting release rates of P and internal P loading (NĂŒrnberg et al 1986;NĂŒrnberg 1988;Carter and Dzialowski 2012;Tammeorg et al 2017).…”
Section: Implications For Lake Water Management By Aeration Treatmentmentioning
confidence: 99%
“…High phosphorus concentrations in the lake water persisted after the dairy sewage flow was stopped, which was due to permanent anoxia of the over-bottom water and consequently limited ability of the sediment to bind P. In the anoxic hypolimnion, 30% of the P can form complexes with iron, and another 30% can be incorporated into the phytoplankton biomass, while the remaining phosphorus is dissolved in water. Phosphates released by desorption and during organic matter decomposition in the bottom sediments have diffused toward the over-bottom water layer, and later to the trophogenic layer as a result of vertical transport [42][43][44]. In MiƂkowskie Lake, despite high primary production (strong oxygen oversaturation in water, high pH, low water transparency, and high organic matter content), the total depletion of mineral phosphorus in the water was noted at the end of summer stagnation.…”
Section: Reduction Of Internal Sources Of Pollutionmentioning
confidence: 99%